2007
DOI: 10.1007/s10549-007-9766-6
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor α, BRCA1, and FANCF promoter methylation occur in distinct subsets of sporadic breast cancers

Abstract: Estrogen receptor α (ER) and its ligand estrogen play vital roles in the development, progression and treatment of breast cancer. An increasing number of studies have also provided evidence linking disruption of the Fanconi anemia/BRCA cascade to breast cancer. Our objectives were to examine the methylation status and expression profiles of ER, correlate the findings with BRCA1 and FANCF methylation and map the critical CpGs for ER expression. We found that the CpG islands in the 5′ region of the ER gene are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
3
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 25 publications
4
57
3
1
Order By: Relevance
“…They also found that methylation in tumor with higher grade is significantly higher than that in lower grade tumors. Meanwhile, a significant correlation between the hormone receptors and methylation status was also reported (Wei et al, 2008) With regard to the methylation status of ER3, 41.7% of the samples were methylated in our study, and no significant correlation was found between ER3 methylation status and prognostic factors, such as tumor size and grade, lymph node involvement, and IHC markers, including ER, PgR, HER-2, and p53. Higher methylation rate of ER3 in the right breast of premenopausal patients was prominently significant.…”
Section: Methylation Scorecontrasting
confidence: 50%
See 2 more Smart Citations
“…They also found that methylation in tumor with higher grade is significantly higher than that in lower grade tumors. Meanwhile, a significant correlation between the hormone receptors and methylation status was also reported (Wei et al, 2008) With regard to the methylation status of ER3, 41.7% of the samples were methylated in our study, and no significant correlation was found between ER3 methylation status and prognostic factors, such as tumor size and grade, lymph node involvement, and IHC markers, including ER, PgR, HER-2, and p53. Higher methylation rate of ER3 in the right breast of premenopausal patients was prominently significant.…”
Section: Methylation Scorecontrasting
confidence: 50%
“…A survey of the literature shows that the reported frequency of CpG island methylation in the promoter region of ER-α in Chinese (Zhao et al, 2008), Turkish (Buyru et al 2009), North American and Korean (Lee et al, 2008), American (Wei et al, 2008), and Indian (Mirza et al, 2007) women with breast cancer is different, and a diverse impact on the prognosis of cancer has also been reported in different countries. The frequency of methylation in different ER in the current study is not exactly similar to the previously reported studies, but considerable similarities of methylation frequency of each ER, i.e.…”
Section: Methylation Scorementioning
confidence: 99%
See 1 more Smart Citation
“…As an example, DNMT1 recruits HDAC1 to the estrogen receptor ␣ (ESR1) promoter to turn off expression of ESR1 in MDA-MB-231 breast cancer cells (50,75). Cotreatment of cells with TSA and the methyltransferase inhibitor 5-aza-dC reactivates transcription of ESR1 (22,71). In addition, it has been reported that SIRT1 associates with the Ecadherin (CDH1) promoter, which can also be silenced in MDA-MB-231 cells (27,56).…”
Section: Dnmt1 Is Acetylated In Vivo and In Vitromentioning
confidence: 99%
“…Ongoing work is attempting to identify "phenocopies" of BRCA1-associated breast cancers in hopes of distinguishing tumors with intact BRCA1 genes but therapeutic vulnerabilities [e.g., to poly(ADP-ribose) polymerase-1 (PARP1) inhibitors] similar to those of tumors with mutated BRCA1. The potential role of BRCA1 methylation in non-BRCA1 (mutation)-associated breast carcinomas has been difficult to clearly characterize, despite the identification of methylated BRCA1 in larger subsets of basal-like and familial non-BRCA1 (mutation)-associated than in hereditary BRCA1 breast tumor cells (8,9). Defining the characteristics of BRCA1-associated tumors has been challenging (10); perhaps, the novel classification system used by Wong et al will help to shed light on this confusion and permit a clearer focus on the role of epigenetic mechanisms.…”
mentioning
confidence: 99%